Analysis of the Effect of Customer Relationship Management, Service Quality and Word of Mouth on e-Commerce Customer Loyalty through Customer Satisfaction as a Mediator - Muphimin, Muphimin; Rachbini, Widarto (Dinasti Publisher, 2024)
Customer satisfaction is a comprehensive assessment of service and as a result of the comparison between customer expectations and perceptions of actual service performance. The purpose of this study is to see the effect of the independent and dependent variables, using quantitative methods with the help of SmartPLS software. The results of this study indicate that CRM directly affects SQU and LOY, the SQU variable affects SAT and SQU has no effect on LOY, the WIM variable affects SQU and LOY, and SAT affects LOY. In indirect testing, the independent variables, namely CRM, SQU, and WOM, have an effect on SAT which is moderated by LOY.